A two year echocardiographic follow-up of patients with chronic total occlusion treated with percutaneous coronary intervention or receiving only medical therapy. (25th November 2020) - Juricic, S; Petrovic, O; Tesic, M; Dobric, M; Dikic, M; Mehmedbegovic, Z; Zivkovic, M; Vukcevic, V; Aleksandric, S; Milasinovic, D; Tomasevic, M; Orlic, D; et al.
Abstract: Background: Percutaneous coronary intervention of chronic total occlusion (PCI CTO) can reduce angina and the need for bypass surgery, however, it is still not clear how it effects the myocardial function. Conventional echocardiography is subjective and experience-dependent while tissue Doppler imaging together with strain imaging provides a more objective assessment of myocardial contractility. Purpose: Our aim was to access the effectiveness of percutaneous coronary intervention (PCI) along with optimal medical therapy (OMT) on myocardial function. Methods: We compared two groups of patients. The first group of patients underwent PCI CTO with OMT while the second group of patients only received OMT (control group). The echocardiographic exam was performed before randomization and after 24 months of follow-up. Doppler time intervals- isovolumetric relaxation time (IVRT), isovolumetric contraction time (IVCT) and ejection time (ET) were measured from mitral inflow and left ventricular outflow Doppler tracings. Myocardial performance index (MPI) is equal to the sum of the IVRT and IVCT divided by the ET. Velocity of early mitral filling wave (E) was measured and divided by average peak early diastolic annular velocity (e'). Peak longitudinal strain was assessed in 17 left ventricular segments. Time intervals from start Q/R on electrocardiogram to peak negative strain during the cardiac cycle were assessed. Mechanical dispersion was defined as the standard deviation of this time interval from 17 left ventricular segments, reflecting myocardial contraction heterogeneity Results: Comparing the groups at follow up, there was no significant change in ejection fraction (EF), diastolic function, and mechanical dispersion, however, there was improvement in GLS and MPI (Table 1). Conclusion: Global longitudinal strain as a parameter of systolic function and Myocardial performance index as a parametar of global systolic and diastolic function are sensitive markers that can detect subtle improvement in myocardial function after recanalisation of CTO. Funding Acknowledgement: Type of funding source: None